Historical Background of the Assessment of Vestibular Function: An Overview - Rania Abdulfattah Sharaf; Rudrapathy Palaniappan (International Journal of Pharma and Bio Sciences, 2020)
Caloric, rotational and posturography testing remains the mainstay of vestibular assessment. This study aimed to present the historical review of various balance measurement systems. The electronic databases including PubMed and Web of Science and were searched for relevant articles. This review has included all the relevant past studies that used different balance assessments in patients with vestibular disorders. There are four major balance assessment systems available in the literature (e.g., Caloric testing, post urography, rotational chair test, and vestibular evoked myogenic potential testing). Caloric stimulus, although non-physiological has the advantage of testing each ear separately. Rotational testing stimulates both labyrinths simultaneously. It remains popular because the stimulus is precise, physiological and can be applied without much patient discomfort. Posturography is still developing in its clinical use. The advent of computers together with modern methods of recording responses such as evoked potentials, eye movement, and postural sway has altered the precise way testing is performed. Previous experiments have demonstrated that caloric nystagmus can be elicited in the absence of the gravitational field that is required for convection current. In conclusions, different balance assessment systems have been evolved over a period of times. The caloric testing, posturography, vestibular evoked myogenic potential testing, and rotational chair tests were common balance assessment systems used in the literature. This is the comprehensive review of past studies that reported the usage of different balance assessments in patients with vestibular disorders. Future studies should summarize the evidence of recent advances in the assessment of the balance system in healthy and pathological conditions.